KOMPOSISI JENIS TUMBUHAN BERGUNA DI HUTAN KOTA KECAMATAN BATULICIN KABUPATEN TANAH BUMBU - Mahriana Mahriana; Kissinger Kissinger; Rina Kanti (Jurnal Sylva Scienteae, 2020)
Urban forests are trees that stand alone or in groups or woody vegetation in urban areas which basically provide two basic benefits for the community and the environment, namely conservation benefits and aesthetic benefits. Urban forests must be functional, meaning that plants can function in environmental management. The purposes of this study are to identify useful plants, species composition and stand density, potential of useful plant, to analyze plant vegetation in the Batulicin city forest. The object that was observed was the plants in the city forest. The results showed that the results of species composition found were 26 species of trees and regeneration. The highest number of useful plant species was obtained at 14 species and 11 species. The highest useful plant potential at the tree level is 42.71 m³ / ha and the pole level is 36.88 m³ / ha. The highest INP of seedlings is Mangifera idica, Peronema canencens, Mimusps elengi. Rubber, Swietania macrophylla and Peronema canencens  level. Level of Rubber pole, Anthocephalus cadamba and Swietania macrophylla. Levels of Samanea saman, Paraserianthes falcataria and Peronema canencens trees. (H ') contained in the urban forest classified as medium for seedling level 2.89, stake 2.31, pole 2.64 and tree 1.827.Key word: composition; species